Jews Don't Count : How Identity Politics Failed One Particular Identity - Baddiel, David (London TLS Books, 2021)
How identity politics failed one particular identity. 'a must read and if you think YOU don't need to read it, that's just the clue to know you do.' SARAH SILVERMAN 'a masterpiece.'STEPHEN FRY
Keywords: Social justice--Religious aspects--Judaism -- Antisemitism -- Jews--Social conditions